The reserpine effects on the gonadotrophic cells of the male common carp Cyprinus carpio (Osteichtyes: Cyprinidae) - González-Segura, Lilian (2004)
The secretion of gonadotropins (GtH) in goldfish and carp, is stimulated by GtH-releasing hormone (GnRH) and is inhibited by dopamine. Studies with antidopaminergics have demonstrated to be effective in order to stimulate the spermiation and the ovulation in different species of teleosts. The reserpine, a drug that deplets the dopamine, has shown to stimulate the spermiation in the common carp. We report here, the effects of reserpine on the number and volume of gonadotrophic cells of the common carp. Eight injections of reserpine alone, at doses of 0.5, 1.0 or 1.5 mg/ml/kg of body weight and at intervals of 48 hours, caused an increase in the number and volume of gonadotrophic cells. The dose 0.5 mg/ml/kg, presented an increase in the number and volume of gonadotrophic cells of 382% and 123%, respectively, above the control group. The dose 1.0 mg/ml/kg, showed an enhanced number and volume of gonadotrophic cells of 704% and 152%, respectively. With the dose 1.5 mg/ml/kg increase in number (171%) and volume (106%) of gonadotrophic cells was lower. The gonads of the experimental groups had an abundance of advanced states of spermatogenesis. Our results show that eight intraperitoneal injections of reserpine were responsible for an increase in gonadodrophic cell, number and volume.